Expert consensus-based recommendations on the use of photodynamic therapy in actinic keratosis patientsCapsule Summary - Vishal A. Patel, MD; Sarah T. Arron, MD; Brian Berman, MD, PhD; M. Shane Chapman, MD, MBA; Anokhi Jambusaria-Pahlajani, MD; George Martin, MD; Anthony M. Rossi, MD; Todd Schlesinger, MD; Nathalie C. Zeitouni, MDCM; Neal Bhatia, MD (JAAD International)
Background: Current actinic keratosis (AK) treatment guidelines are controversial and incomplete, leaving an unmet need for clearer and more in-depth guidance on the usage of photodynamic therapy (PDT) in AKs. Objective: To gain consensus on the use of PDT for AKs using a modified Delphi method. Methods: Consensus statements were developed after a literature review of topics surrounding PDT and AKs. Ten panelists voted through electronic questionnaires rating each statement on a three-point Likert-type scale: strongly agree, agree, and disagree. Consensus was established when ≥70% of panelists strongly agreed on the statement. Statements that did not meet the threshold were revised after each round of voting and sent out for the next round of voting. A virtual meeting was held after 2 rounds of voting to discuss outstanding statements. Results: Three modified Delphi rounds were completed in total and 1 virtual meeting was held. All 10 experts responded to all rounds of voting. A total of 55 statements established consensus with the ≥70% majority requirement necessary. Limitations: Recommendations are based on expert opinions. Conclusion: The results from this consensus panel are intended to bridge gaps in the existing guidelines and will continue to evolve.